Étude des caractéristiques psychométriques des indicateurs de stress et de la résolution de problèmes sociaux chez les stagiaires en enseignement: Étude des caractéristiques psychométriques des indicateurs de stress et de la résolution de problèmes sociaux chez les stagiaires en enseignement - Montgomery, Cameron; Bujold, Neree; Bertrand, Richard; Dupuis, Francois (Canadian Journal of Higher Education, 2002)
This article describes the methodology of the adaptation and validation of measurement instruments dealing with stress and social problem solving ability. Several theoretical frameworks, other models of stress and social problem solving, and an item analysis of two instruments will be presented. The following research questions will be addressed: what are the psychometrical characteristics of the stress indicators in student teachers? What are the psychometrical characteristics of the social problem-solving ability indicators in student teachers? We will also present the results of factor analyses. The validation of these instruments will allow to more specifically study the effect of stress on student teachers. Furthermore, it is a first step towards future research aiming at helping teacher educators involved in the student teacher education process to find new stress management strategies and adapt education to student teachers' needs.